From Acute to Chronic Tinnitus: Pilot Data on Predictors and Progression - Vielsmeier, Veronika; Santiago Stiel, Ryan; Kwok, Pingling; Langguth, Berthold; Schecklmann, Martin (Frontiers in Neurology, 2020)
Translational tinnitus research is hampered by a gap between animal research, that is focussed primarily on acute tinnitus and clinical research that deals primarily with chronic tinnitus. Moreover, little is known about the transition from acute tinnitus to chronic tinnitus. In this study, we are attempting to close this gap by presenting prospective pilot data of patients with acute tinnitus followed by tracking their course of development over a period of six months. 49 patients presenting with acute tinnitus (duration < 28 days) were recruited in two clinics. We recorded demographic and clinical tinnitus related data as well as personality, health-related, treatment and life-style data during first appearance in the clinic and again three and six months later. Standard audiograms were performed at the first and the second visit. 9 (18.4%) patients showed full remission of their tinnitus. These patients differed from patients with chronic course of tinnitus by shorter tinnitus duration, lower fear-related hyperacusis, proportion of female gender, increased ear pressure, and lower levels of alcohol consumption. Among the patients with a chronic course of tinnitus, there was no change in tinnitus characteristics. However, their tinnitus distress improved moderately over time. These preliminary data are in line with earlier studies, that have shown that only a small proportion of those patients who present in the clinic with acute tinnitus, experience a full remission. The results of this study can be of service in deducing hypotheses for the transition from acute in chronic tinnitus and in developing designs for interventional studies.